Intention Model of Waste Management Education Concept based on Green Campus in Brawijaya University - Sri Muljaningsih; Ajeng Kartika Galuh (Indonesian Journal of Environment and Sustainable Development, 2018)
This research was aimed to analyze the behaviors of Brawijaya University’s stakeholders through the intention in managing waste. Considering that campus is a place of education, the analysis of the intention associated with the educational theory in cognitive, affective and psychomotor domains. Thus, this research implementation was supported by intention model. The objects of this research were the stakeholders of Brawijaya University consisting of students, lecturers, and staffs. This research was done using survey method with a total of 120 respondents. The analysis was conducted using a path analysis method with trimming. Given that the number of variables used was quite a lot, the data were first analyzed using a factor analysis method and then followed with a path analysis method. The results of the path analysis on Model 1 showed that the significant variables to the intention of managing waste were cognitive and behavioral control variables. The indicators of cognitive variable as knowing the types of waste and the economic benefits of waste. As for Model 2, the intention of managing waste significantly influenced the realization of the green campus  varibles. The indicators of managing waste intention as intention to help manage waste in Brawijaya University, and then the indicators of green campus varible as the emerge of wise thoughts.  As the suggestion, rules or policies on waste management are highly required to be established in Brawijaya University so that the stakeholders are willing to manage and process waste.Keywords: Affective and psychomotor domains, Brawijaya University’s stakeholders, Cognitive, Green campus, Waste management intention model